Pengaruh Citra Merek, Cita Rasa, Dan Kepercayaan Terhadap Kepuasan Dan Loyalitas Pelanggan Pada Pelanggan Roket Chicken Kaliwungu - Bambang Sutedjo; Dwi Hariyanti Ridho Saputri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
After the Covid-19 pandemic, the Indonesian economy began to improve and develop again as before. Many businesses in the culinary industry have encouraged companies to compete and survive by producing good quality food to achieve customer satisfaction and loyalty. The large number of food industries and competition, makes consumers consider product quality / taste according to their needs and expectations, one of which is the Roket Chicken Kaliwungu fast food restaurant. This study aims to determine the effect of brand image, taste and trust on customer satisfaction and loyalty of Rocket Chicken Kaliwungu. Quantitative research methods. Samples were taken by purposive sampling method. A sample of 100 Rocket Chicken Kaliwungu customers used a questionnaire. Data analysis used statistical tests (multiple linear regression). Based on research and discussion, it is known that brand image, taste, trust have a significant and positif influence on customer satisfaction, and satisfaction has an effect on customer loyalty. Keywords: Brand Image, Taste, Trust, Satisfaction, Loyalty